Adding long-term availability, obfuscation, and encryption to multi-cloud storage systems. (January 2016) - Celesti, Antonio; Fazio, Maria; Villari, Massimo; Puliafito, Antonio
Abstract: Nowadays, storage services offer a new way for Cloud providers to do business. This new trend is proved by the number of Cloud storage providers that are continuously appearing on the market. By now, using Cloud storage services is becoming a common practice for end-users. However, the current Cloud storage providers do not offer any guarantees regarding long-term availability and privacy. In fact, data stored in the Cloud could be locked-in, lost, or violated in terms of privacy. In this work, we present an innovative system that on one hand allows end-users to simultaneously rely on different Cloud storage providers in a transparent way and on the other hand to enforce long-term availability, obfuscation, and encryption. Our system is highly reliable, in fact, if a provider is not temporarily or permanently available, end-users continue accessing their data in a secure way. In addition, only the end-users have the full control of the overall security of their data and no sensitive information are disclosed to Cloud storage providers. Several experiments allow us to discuss the performance of our system compared against existing solutions.